ASSESSING THE IMPACT OF CORPORATE CULTURE ON ENTERPRISE PERFORMANCE IN ENTERPRISES - Omanova Nargiza Rustam qizi (Innovation Science and Technology, 2025)
Corporate culture plays a crucial role in shaping enterprise performance, inﬂuencing factors such as employee engagement, productivity, and overall business success. This study explores the impact of corporate culture on enterprise performance by examining key cultural components, including leadership style, organizational values, communication patterns, and employee motivation. The research evaluates how a strong and well-defned corporate culture contributes to operational efciency, innovation, and competitive advantage. Additionally, it highlights potential challenges organizations may face due to weak or misaligned corporate cultures. By analyzing real-world case studies and empirical data, this study provides insights into best practices for fostering a corporate culture that enhances business performance and sustainability. The fndings aim to assist enterprises in developing strategic approaches to culture management, ultimately leading to improved fnancial and operational outcomes.